2021
DOI: 10.1177/02711214211027625
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Interventions for Young Emergent Bilingual Children: A Systematic Review of Experimental and Quasi-Experimental Studies

Abstract: Vocabulary plays a critical role in later reading achievement of emergent bilingual children (EBC) who are learning two languages. Given emerging vocabulary intervention research for EBC, we synthesize studies on vocabulary interventions designed for preschool and kindergarten EBC to provide the cumulative knowledge on the following dimensions: (a) EBC’s characteristics, (b) features of selected target words and books, (c) critical components of vocabulary interventions, and (d) the overall effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The finding that they learned words that had been used actively in the intervention is promising, and also expected in light of previous studies of shared book reading (Wasik et al, 2016) and the Lexicon Pirate method (Motsch and Ulrich, 2012). The intervention method included several factors that have proved beneficial for word learning in previous studies, e.g., multiple exposures over time (Goldin-Meadow et al, 2014; Steele, 2020), word meanings put into a relevant context with clear explanations (Kong and Hurless, 2021), and explicit use of word learning strategies (Motsch and Marks, 2015). The group intervention format may also have influenced word learning positively, as this gave the children opportunities to discuss with peers as well as with adults (Steele and Mills, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that they learned words that had been used actively in the intervention is promising, and also expected in light of previous studies of shared book reading (Wasik et al, 2016) and the Lexicon Pirate method (Motsch and Ulrich, 2012). The intervention method included several factors that have proved beneficial for word learning in previous studies, e.g., multiple exposures over time (Goldin-Meadow et al, 2014; Steele, 2020), word meanings put into a relevant context with clear explanations (Kong and Hurless, 2021), and explicit use of word learning strategies (Motsch and Marks, 2015). The group intervention format may also have influenced word learning positively, as this gave the children opportunities to discuss with peers as well as with adults (Steele and Mills, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are indications that theme-based multimethod interventions – combining e.g., direct teaching of word meaning with activities that promote the active use of words within the context of a theme – are advantageous for children with below average vocabulary in general (Christ and Wang, 2011). A combination of different approaches has also been suggested to enhance the effect of vocabulary intervention for multilingual children, for example the use of explicit teaching of semantic meaning together with interactive discussion where the child is encouraged to participate actively (Kong and Hurless, 2021). The intervention delivered in this study is theme-based in the sense that target words are selected based on themes, and includes systematic use of different strategies and activities.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review focusing on vocabulary interventions for young emergent bilingual children has demonstrated the effectiveness of utilizing storybooks as valuable tools for teaching vocabulary [32]. Among the various didactic approaches using storybooks, one that aligns with all key characteristics for effective vocabulary instruction is known as IBR.…”
Section: Interactive Book Reading As An Approach For Effective Vocabu...mentioning
confidence: 99%